2012
DOI: 10.1103/physreva.85.023618
|View full text |Cite
|
Sign up to set email alerts
|

Penetration of a vortex dipole across an interface of Bose-Einstein condensates

Abstract: The dynamics of a vortex dipole in a quasi-two dimensional two-component Bose-Einstein condensate are investigated. A vortex dipole is shown to penetrate the interface between the two components when the incident velocity is sufficiently large. A vortex dipole can also disappear or disintegrate at the interface depending on its velocity and the interaction parameters.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Advances in spatiotemporal optical trap control in BECs [27][28][29] now enable a broad range of superfluid dynamics experiments, and the possibility of studying detailed vortex motion is increasingly within reach of current technology. In recent numerical work [30], it was shown that a vortex dipole at sufficiently high velocity could cross an interface in an immiscible two-component BEC. At lower velocities, the dipole either disappeared or disintegrated, with the remnants moving along the interface.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in spatiotemporal optical trap control in BECs [27][28][29] now enable a broad range of superfluid dynamics experiments, and the possibility of studying detailed vortex motion is increasingly within reach of current technology. In recent numerical work [30], it was shown that a vortex dipole at sufficiently high velocity could cross an interface in an immiscible two-component BEC. At lower velocities, the dipole either disappeared or disintegrated, with the remnants moving along the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The parameters corresponding to figure 8 can be taken as m 1 =1.42×10 −25 kg, m 2 =1.45×10 −25 kg, μ m =1.02, N 1 ≈3.28×10 6 , N 2 ≈3.27×10 6 , n 0 =50, ω 0 =2π×2 Hz, a 0 =7.70 μm, V 0 =1.32× 10 −31 J, (x 0 , y 0 )=(0.98,0) mm, d=7.70 μm, 0.068 mm s 1 u = -, a 11 ≈99.24a B ≈5.25 nm, a 22 » a 100. 40 5.31 nm B » , and a a a 89.58 4.74 nm 12…”
Section: Vortex Shedding From the Obstaclementioning
confidence: 99%
“…In component 2, it is significant that the two point quantized vortices in a pair, which shed from the moving obstacle potential at a time, have the same circulation. The quantized vortex is the topological defect of order parameter and the circulation is quantized to h/m j [9,40] with h being the Planck's constant. Here, the symbols + and − denote the clockwise and counterclockwise circulations of quantized vortices.…”
Section: Vortex Shedding From the Obstaclementioning
confidence: 99%
See 1 more Smart Citation
“…We create a vortex dipole on one side of the magnetic regions, and it moves toward the phase boundary. When a vortex dipole has a sufficiently large velocity, it can penetrate the phase boundary [22]. Passing through the phase boundary, the vortices experience a change in the magnetic phase, and consequently, the topological properties of the vortices are forced to change.…”
Section: Introductionmentioning
confidence: 99%